Primary Health Care in the Peruvian Amazon during COVID-19: perspectives from Indigenous nurse technicians - Pesantes, M. Amalia; Cardenas Palacios, Cynthia; Hewlett, Christopher; Maake, Caroline (Frontiers in Tropical Diseases, 2023)
Introduction Indigenous peoples of the Amazon basin, in Peru and elsewhere, suffered disproportionately from the impacts of the COVID-19 pandemic. In part, this was due to an initial lack of support by the Ministry of Health, who did not prioritize their care despite their vulnerable situation. Consequently, during the first wave of the pandemic, health professionals in public health facilities in Amazonian Indigenous communities had to handle the disease with limited information and resources. This article analyzes the actions carried out by Indigenous nurse technicians during the first wave of the pandemic. Methods Recurrent semi-structured interviews with six Indigenous nurse technicians focusing on their measures toward disease prevention and caring during the first wave of the COVID-19 pandemic in the Atalaya province, Ucayali region, in the Peruvian Amazon. Results Nurse technicians worked closely with local authorities and volunteer health promotors. The limited resources they had at the health facilities, coupled with no training about how to treat COVID-19 symptoms led them to resort to their knowledge of traditional Indigenous medicine in combination with biomedical approaches, and support from Indigenous healers. Our analyses shows that this approach proved essential to alleviate symptoms and prevent complications and new infections. Conclusions The actions implemented by the Indigenous nurse technicians strongly contributed to the management of COVID-19 in their Indigenous communities, being both effective and culturally appropriate. Our data is in support of a health provision concept that bridges medical knowledge systems in contexts of diversity, avoiding a view on Indigenous health practices as antagonistic or in competition with biomedical practices provided by public health services.